Viscoelastic cohesive zone modeling for mode II fracture between propellant and insulation. (April 2022) - Cui, Huiru
Abstract: The performance of debonding interface between the solid propellant and insulation in the solid rocket motor which on the warship is a function of time that depends on the time regime chosen to elicit it. In this paper, a new time dependent cohesive zone model (CZM) is introduced with N Maxwell models which are connected in parallel and let the input, time independent traction transform into the time dependent one. Stretch test with constant velocity, cyclic loading and relaxation test were applied in a simple 2D cohesive element. The acquisition of the model parameters was introduced by Single lap-joints (SLJ) test. A semi-section of vertical storage motor was modeled and analyzed considering the debonding interface between the solid propellant and insulation under a set of regular and irregular waves. The introduced time dependent CZM and the results of the integrity analysis are useful and meaningful for further research on vertical storage solid rocket motor.